Therapeutic Futility in Nursing: A Focus Group - João V. Vieira MSc; Sérgio Deodato PhD; Felismina Mendes PhD (SAGE Publishing, 2022)
Introduction: The implementation of futile nursing interventions seems to be a persistent problem in adult intensive care units. Understanding this phenomenon can contribute to its prevention and all deleterious effects associated with it. Objective: To identify the perceptions of expert nurses from adult intensive care units about therapeutic futility in nursing. Methods: This study consists of a conventional content analysis. Data was collected through a focus group interview that included five expert nurses in adult intensive care, with a minimum of fifteen years of professional experience in intensive care. To analyze the information, the technique of thematic categorical analysis was used, according to Bardin. Results: Four central categories were identified for the topic under study, for which several subcategories were identified that allow a better understanding of this phenomenon. Conclusion: Adult intensive care expert nurses advocate that therapeutic futility in nursing is a reality perceived by teams and families, which should be avoided due to the risk of potentiating the implementation of ethically reprehensible care.